Role of regular medical visits in mitigating increased suicide risk during the early COVID-19 pandemic in Kobe, Japan - Daisuke Miyamori; Yasushi Nagasaki; Shuhei Yoshida; Saori Kashima; Wataru Omori; Kei Itagaki; Masanori Ito (BMC Primary Care)
Abstract Background Japan has one of the lowest COVID-19 death rates, while the annual suicide rate in 2020 has risen for the first time since 2007. This study aimed to identify high-risk populations and assess the impact of medical visits on suicide trends post-COVID-19 pandemic in Japan. Method This quasi-experimental study analyzed a population-based database from Hyogo Prefecture (2012–2022). Interrupted time-series analyses identified level and trend changes in monthly suicide rates per 1 million population during the exposure period (2020–2022) versus the control period (2012–2019). Regular visits to primary care and psychiatry stratified analysis. Results 2181 cases were analyzed, with two-thirds male and a median age of 54. Primary care physicians and psychiatric history were present in 69% and 40% of patients. The study found significant level changes in suicide rates overall (4.14, 95% CI: 1.70, 6.58) among individuals without regular primary care physician visits (2.83, 95% CI: 1.35, 4.32) and without psychiatric visits (2.85, 95% CI: 0.56, 5.14). In contrast, no significant changes were observed in individuals with regular primary care (0.99, 95% CI: -0.78, 2.76) or regular psychiatric visits (0.59, 95% CI: -0.98, 2.16). The trend changes were not significant in any of the groups. Conclusion This study suggests that a history of attending a medical institution may have prevented the rapid increase in suicides during the early stages of the COVID-19 pandemic.